The extent to which educational administration departments in Jordanian public and private universities are committed to performing their social responsibility from the point of view of some faculty members - Shboul, Monther Qasem (Journal of Educational and Psychological Sciences, 2021)
The study aimed to find out the extent to which the educational administration departments in the Jordanian public and private universities are committed to performing their social responsibility from the point of view of the faculty members in them. The descriptive analytical method was used. In order to answer the questions of the study, the arithmetic averages, standard deviations, and rank were extracted to the degree of commitment of the educational administration departments in the Jordanian public and private universities to perform their social responsibility, and the triple analysis of variance was used to test the significance of the differences between the variables, in light of the responses of the faculty members to the fields of study, after classifying them within the following levels Gender (male, female), experience (less than 10 years, 10 years or more) and university qualifications (public and private). A tool was developed, consisting of (21) paragraphs, and distributed to the study sample members of the 66), a faculty member in the educational administration departments in Jordanian and private universities for the academic year 2020/2021, and it included three areas: academic programs, scientific research, and activities and events. The study concluded that the commitment of the educational administration departments in the public and private Jordanian universities to perform their social responsibility obtained an overall average (77¸1 out of 3), i.e. a degree of commitment (medium), and at the level of the three domains; The field of academic programs got the highest average (4.¸2), then the field of scientific research with an average (71,1), both with a degree of commitment (medium), and finally activities and events with an average of (58.1) and a degree of commitment (low). The results also showed that there were no differences Statistically significant at the significance level (α = 0.05) between the arithmetic averages of the responses of the study sample members to the tool domains as a whole, and to the variables of gender, experience, and university status. Based on the results, the study may recommend conducting a study on the possibility of integrating social responsibility within the academic accreditation standards.